Soil Bacterial Community Along an Altitudinal Gradient in the Sumaco, a Stratovolcano in the Amazon Region - Díaz, Magdalena; Quiroz-Moreno, Cristian; Jarrín-V, Pablo; Piquer-Esteban, Samuel; Monfort-Lanzas, Pablo; Rivadeneira, Erika; Castillejo, Pablo; Arnau, Vicente; Díaz, Wladimiro; Sangari, Félix J.; Molina, C. Alfonso (Frontiers in Forests and Global Change, 2022)
Our study is a pioneering exploration of the microbiome in the soil of the Sumaco stratovolcano and an assessment of the effects of an elevational gradient and related physicochemical soil parameters on richness and community structure. The Sumaco, as an isolated Amazonian stratovolcano, may be among one of the least studied ecosystems in Ecuador and perhaps the Amazon region. Universal patterns remain unresolved or available information inconclusive to establish a supported consensus on general governing processes by which elevation and its associated environmental gradients may determine the microbial richness and community structure. We tested a recent proposal on how microbial diversity responds to montane gradients, placing a central role in soils as potentially independent of altitude along an elevational gradient. Correlations and effects among soil physicochemical parameters and altitude were contrasted against richness and community structure through quantitative ecology. The most informative physicochemical parameter in our assessment of bacterial community structure was neither pH nor altitude, but sulfur, which was mostly independent of the other tested parameters. We established a positive effect of richness by parameters associated with metallic cations such as Mn2+, and CEC, which were negatively correlated to altitude and pH. The possible relation between the significant role of sulfur on bacteria community structure with the unique geological origin of the Sumaco stratovolcano should be examined in the context of specialized sulfur metabolisms and additional information on community structure and environmental constraints. Our study establishes an initial baseline for further explorations of microbial diversity in this unexplored tropical stratovolcano